The Role of Big Data Analytics in the Investigation of Corruption Offences - CHYSTIAKOVA, Anastasiia; PODLIEHAIEV, Kostiantyn; KHORONOVSKYI, Oleg; SOKUR, Tetiana; KUBARIEV, Ivan (Revista Jurídica Portucalense, 2025)
The article deals with the integration of big data (BD) analytics in the investigation of corruption offenses and assesses its potential to detect complex criminal schemes. The use of large data volumes, such as financial transactions, communication patterns, and public records, significantly improves the effectiveness of investigations. Data analysis makes it possible to reveal hidden connections and anomalies, which provides new tools for the fight against corruption. The article combines legal analysis with technological innovation and explores the legal and ethical issues that arise when using such technologies. It focuses on how BD can be integrated into the legal process within existing legal systems. The academic novelty is the study of the changes that BD analytics bring to the corruption investigation practices. The study also identifies data protection and compliance challenges that require the creation of an appropriate legal framework and the development of specialized skills.